Trans-anal irrigation in patients with multiple sclerosis: Efficacy in treating disease-related bowel dysfunctions and impact on the gut microbiota: A monocentric prospective study. Issue 3 (July 2022) - Ascanelli, Simona; Bombardini, Cristina; Chimisso, Laura; Carcoforo, Paolo; Turroni, Silvia; D'Amico, Federica; Caniati, Maria Luisa; Baldi, Eleonora; Tugnoli, Valeria; Morotti, Chiara; Valpiani, Giorgia; Bazzocchi, Gabriele
Background: Constipation and faecal incontinence are not so uncommon in patients with multiple sclerosis, impairing quality of life. The gut microbiota is altered in multiple sclerosis patients and likely contributes to disease pathogenesis. Trans-anal irrigation has been proven to allow treatment of neurogenic bowel dysfunction and may affect gut microbiota. Objectives: The primary outcome was trans-anal irrigation effectiveness on constipation and faecal incontinence. The secondary outcome was gut microbiota profiling compared to healthy subjects and during trans-anal irrigation adoption. Methods: We conducted a prospective cohort study on multiple sclerosis patients, screened with Patient Assessment of Constipation Quality of Life questionnaire before undergoing constipation and faecal incontinence scoring, abdomen X-ray for intestinal transit time, compilation of food and evacuation diaries and faecal sample collection for gut microbiota analysis before and after 4 weeks of trans-anal irrigation. Results and Conclusions: Eighty patients were screened of which nearly half had intestinal symptoms. The included population (n = 37) was predominantly composed of women with significantly longer disease duration, higher mean age and disability than the excluded one ( p  < 0.05). Twelve patients completed the trans-anal irrigation phase, which led to significant improvement of bowel dysfunction symptom-related quality of life, increase in gut microbiota diversity and reduction of the proportions of pro-inflammatory taxa ( p  < 0.05). Trans-anal irrigation was safe, satisfactory and could help counteract multiple sclerosis-related dysbiosis.